Wall shear stress estimated by 3D-QCA can predict cardiovascular events in lesions with borderline negative fractional flow reserve. (April 2021) - Tufaro, Vincenzo; Safi, Hannah; Torii, Ryo; Koo, Bon-Kwon; Kitslaar, Pieter; Ramasamy, Anantharaman; Mathur, Anthony; Jones, Daniel A.; Bajaj, Retesh; Erdoğan, Emrah; Lansky, Alexandra; Zhang, Jinlong; et al.
Abstract: Background and aims: There is some evidence of the implications of wall shear stress (WSS) derived from three-dimensional quantitative coronary angiography (3D-QCA) models in predicting adverse cardiovascular events. This study investigates the efficacy of 3D-QCA-derived WSS in detecting lesions with a borderline negative fractional flow reserve (FFR: 0.81–0.85) that progressed and caused events. Methods: In this retrospective cohort study, we identified 548 patients who had at least one lesion with an FFR 0.81–0.85 and complete follow-up data; 293 lesions (286 patients) with suitable angiographic characteristics were reconstructed using a dedicated 3D-QCA software and included in the analysis. In the reconstructed models blood flow simulation was performed and the value of 3D-QCA variables and WSS distribution in predicting events was examined. The primary endpoint of the study was the composite of cardiac death, target lesion related myocardial infarction or clinically indicated target lesion revascularization. Results: During a median follow-up of 49.4 months, 37 events were reported. Culprit lesions had a greater area stenosis [(AS), 66.1% (59.5–72.3) vs 54.8% (46.5–63.2), p< 0.001], smaller minimum lumen area [(MLA), 1.66 mm 2 (1.45–2.30) vs 2.10 mm 2 (1.69–2.70), p= 0.011] and higher maximum WSS [9.0 Pa (5.10–12.46) vs 5.0 Pa (3.37–7.54), p < 0.001] than those that remained quiescent. In multivariable analysis, AS [hazard ratio (HR): 1.06, 95% confidence interval (CI): 1.03–1.10, p= 0.001] and maximum WSS (HR: 1.08, 95% CI: 1.02–1.14, p= 0.012) were the only independent predictors of the primary endpoint. Lesions with an increased AS (≥58.6%) that were exposed to high WSS (≥7.69Pa) were more likely to progress and cause events (27.8%) than those with a low AS exposed to high WSS (7.4%) or those exposed to low WSS that had increased (12.8%) or low AS (2.7%, p < 0.001). Conclusions: This study for the first time highlights the potential value of 3D-QCA-derived WSS in detecting, among lesions with a borderline negative FFR, those that cause cardiovascular events. Graphical abstract: Image 1 Highlights: Coronary lesions with fractional flow reserve (FFR) of 0.81–0.85 are associated with an increased risk of cardiac events. High wall shear stress (WSS) appears able to identify lesions with borderline negative FFR that cause adverse events. WSS might be used in the future to detect vulnerable plaques and better stratify cardiovascular risk.